The Critical-Linguistic Critique of the Aesthetic Ideology in the Late Writing of Paul de Man - Spencer, Jeremy (Labyrinth, 2020)
The focus of this essay is Paul de Man's provocative antipathy towards the category of the aesthetic in his late writings on philosophical aesthetics. I introduce de Man's critique of what he terms aesthetic ideology – a form of ideological communication – which he considers manifest in the aesthetics of Schiller in particular but also in more scrupulously critical philosophers. I begin the essay with Benjamin's well known observation that twentieth century fascisms aestheticized political practice as part of a defence of existing property relations. I introduce de Man's critique of aesthetic ideology as a way of developing or elaborating on what are relatively sketchy comments on the relationship aesthetics and politics in Benjamin's earlier essay.